Mixed Acinar-Endocrine Carcinoma (MAEC) Arising in Duodenal Pancreatic Heterotopia - Phoenix D. Bell (Case Reports in Pathology, 2019)
Mixed acinar-endocrine carcinoma (MAEC) of the pancreas is a rare neoplasm, consisting of at least 25%–30% of acinar and neuroendocrine populations. Patients are often middle-aged and present with nonspecific symptoms. Imaging typically reveals a solid lesion in the pancreatic head. Management involves surgical resection and the overall prognosis is variable. Here, we present a case of a 48-year-old male who presented with a MAEC arising from duodenal pancreatic heterotopia. This is the one of the first cases, with histologic evidence, of MAEC arising from pancreatic heterotopia.